PERKEMBANGAN DIAMETER TELUR IKAN BETOK (Anabas Testudineus) YANG DIBERI PAKAN DIPERKAYA VITAMIN E DENGAN DOSIS BERBEDA - Etika, Desmi; Muslim, Muslim; Yulisman, Yulisman (Jurnal Perikanan dan Kelautan, 2013)
The aims of this research was to know the development of egg diameter ofclimbing perch were feed enriched used different dosage of vitamin E. The experimentwas arrenged in a Completely Randomized Design (CRD) with 5 treatments and 3replicated. The treatments was vitamin E (V.E) consist of, V.E0 (0 mg.kg-1) withoutvitamin E, V.E1 (100 mg.kg-1), V.E2 (150 mg.kg-1), V.E3 (200 mg.kg-1), V.E4 (250mg.kg-1) of feed. Parameters observed consist of eggs diameter development, gonadmaturity levels and water quality. The results of study showed that the enrichment of150 mg.kg-1 vitamin E on feed was provided response on the development of the eggdiameter (0.401 mm) and reached gonad spawned stage that showed by the transparantcolour of eggs (mature). Water quality parameter during rearing was still in tolerantrange of climbing perch.